Isolation and characterization of Bacillus sp. HSY32 and its toxin gene for potential biological control of plant parasitic nematode - Peiyu Yan; Shakil Ahmad; Zhixia Xu; He Jia; Renyue Zhang; Jingwen Song; Nazia Manzar; Abhijeet Shankar Kashyap; Wenfei Zhang (Chemical and Biological Technologies in Agriculture)
Abstract Plant parasitic nematodes (PPNs) cause significant damage to crop production worldwide, leading to substantial economic losses. Conventional chemical nematicides are effective but frequently associated with environmental and health hazards. In response, biological control methods, particularly the use of microbial pesticides, have emerged as a sustainable and effective alternative. This study focuses on the isolation and characterization of Bacillus sp. HSY32, a bacterial strain with nematicidal properties, from a tropical rainforest soil sample in Hainan, China. Soil samples were screened for nematicidal activity, which led to the identification of the strain HSY32. Detailed observations using optical and scanning electron microscopy (SEM) revealed that HSY32 forms spores and parasporal crystal structures, which are typically associated with nematicidal Bacillus species. Genomic analysis of HSY32 showed that its genome spans 6,711,949 base pairs and contains 7915 predicted genes, with an average GC content of 35.4%. Phylogenetic analysis, utilizing 16S rRNA sequences and average nucleotide identity (ANI), established that HSY32 is closely related to Bacillus mobilis, a known species within the Bacillus genus. Further genomic analysis using local BLAST identified several toxin genes with high similarity to known nematicidal genes, including cry4Ba, cry50Ba, app6Ba, cry70Bb, and tpp36Aa. To confirm the functionality of these toxin genes, they were cloned into pET-30a expression vectors and expressed in E. coli BL21 (DE3) cells. Among the expressed proteins, the Cry4Ba-like protein, with a molecular weight of approximately 110 kDa, was found to exhibit significant nematicidal activity in bioassays. This protein demonstrated the ability to kill or inhibit the growth of PPNs, indicating its potential as a biological control agent. The successful isolation of Bacillus strain HSY32 and the identification of its novel Cry4-like toxin gene represent a significant advancement in the field of biological control of plant parasitic nematodes. The nematicidal activity of the Cry4Ba-like protein highlights the potential of HSY32 as a source of new biopesticides. Further studies are required to enhance the production and application of these biocontrol agents in agriculture, paving the way for more sustainable and eco-friendly methods to control PPNs. Graphical Abstract